2020
DOI: 10.1002/ange.202008990
|View full text |Cite
|
Sign up to set email alerts
|

Posttranslationally Acting Arginases Provide a Ribosomal Route to Non‐proteinogenic Ornithine Residues in Diverse Peptide Sequences

Abstract: Ornithine is a component of many bioactive nonribosomal peptides but is challenging to incorporate into ribosomal products. We recently identified OspR, a cyanobacterial arginase-like enzyme that installs ornithines in the antiviral ribosomally synthesised and posttranslationally modified peptide (RiPP) landornamide A. Here we report that OspR belongs to a larger family of peptide arginases from diverse organisms and RiPP types. In E. coli, seven selected enzymes converted arginine into ornithine with little p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In addition, studies by Piel’s group have shown that OspR was able to modify three Arg residues to the non-canonical ornithine in another linear brevicidine mimic. In addition, the epimerase OspD could introduce a D-amino acid in this mimic, although the position of the D-amino acid did not match the D-amino acid positions in natural brevicidine (Mordhorst et al 2020 ). These results indicate that there are a variety of RiPP tools available that can potentially be combined to introduce NRP structural features into ribosomal peptides (Fig.…”
Section: Combinatorial Engineering Of Various Modifications Into Lant...mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, studies by Piel’s group have shown that OspR was able to modify three Arg residues to the non-canonical ornithine in another linear brevicidine mimic. In addition, the epimerase OspD could introduce a D-amino acid in this mimic, although the position of the D-amino acid did not match the D-amino acid positions in natural brevicidine (Mordhorst et al 2020 ). These results indicate that there are a variety of RiPP tools available that can potentially be combined to introduce NRP structural features into ribosomal peptides (Fig.…”
Section: Combinatorial Engineering Of Various Modifications Into Lant...mentioning
confidence: 99%
“…Further modification work mainly focuses on the incorporation of D-amino acids, the non-canonical amino acid ornithine, and the mimicking of a fatty acid chain by enzymatic methods. Piel’s group has demonstrated the possibility of introducing D-amino acids and ornithines onto similar linear peptide sequences (Mordhorst et al 2020 ).…”
Section: Combinatorial Engineering Of Various Modifications Into Lant...mentioning
confidence: 99%
See 1 more Smart Citation